Positive psychology towards English learning anxiety among students of secondary school at Sichuan China - Wei, Li; Yasin, Maizura (Human Resource Management Academic Research Society, 2024)
Positive psychology is an emerging field of research in psychology initiated in the United States at the end of the 20th century. Positive psychology is committed to the study of human development potential and virtues, and focuses on the positive factors of human. In China, the "Full-time Compulsory Education English Curriculum Standards" proposed that English learning particularly emphasizes paying attention to each student's emotion, stimulating their interest in learning English, helping them to establish a sense of achievement and self-confidence in learning, enhancing practical ability, and cultivating a spirit of innovation. Positive psychology provides theoretical guidance for secondary school English teaching, and the application of positive psychology has a positive impact on helping students cultivate a positive personality, establishing a harmonious teacher-student relationship, stimulating the motivation and interest in learning English, and forming an active cognitive learning process. Five students and one English teacher in one class of the second grade of secondary school in Sichuan Province participated in this research. On the basis of drawing on relevant research results at home and abroad, the interview method and observation method are used to investigate the current situation of secondary school English teaching, analyze the existing problems, and propose strategies of positive psychology in English teaching from three aspects: teachers, students, and English teaching environment, and prove that the application of positive psychology can promote the development of secondary school English teaching and effectively alleviate students' anxiety about English learning.